The Influence of Travel Experience and Destination Image on Traveller Satisfaction and Intention to Revisit - Naufal Sinatria; Sumadi Sumadi (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to identify the influence of memorable tourism experience variables and destination image on tourist satisfaction and intention to revisit beach tourism in the Special Region of Yogyakarta by developing Stimulus - Organism - Response literature. This research is quantitative and conducted using a survey method. Primary data in this research were obtained through Google Forms and 225 respondents with purposive sampling. Techniques were used to test the proposed model-data analysis using a co-variance-based Structural Equation Model (SEM) with AMOS 25 Software. The results show a direct influence of memorable tourism experiences and destination images on tourist satisfaction and revisit intentions. Tourist attraction managers can use the results of this research to add to the memorable experience of tourists and improve a good image of the attraction to increase tourist satisfaction and intention to revisit